Zukunftsfähiger internationaler Rechtsrahmen für Investitionen in Afrika - Gramlich, Ludwig (Recht in Afrika, 2020)
The future of sustainable development in Africa and for its growing population will depend on investments which might come mostly from abroad attracted by a favourable investment climate (or ecosystem). It is rather doubtful that the actual ('old') international legal framework for investment-related and investment-specific measures which does hardly create an adequate balance between the interests of all important public as well as private stakeholders would meet the requirement of today and tomorrow. But any alterations or improvements must start from the present state of things. So, this study looks at the different levels and various instruments dealing with traditional standards of investment and investor protection, e.g. BITs und TIPs, and at the activities of global, regional and sub-regional organizations (in particular EU and OHADA). Moreover, new developments at global and regional levels are discussed including trends showing a somewhat specific African approach to investment issues ('Africanization'). Finally, a very important topic, i.e. the relation between investment protection and human rights (of investors and of other people negatively affected by relevant activities), is described and assessed in more detail. A second part of the analysis will turn to elaborating on dispute settlement and enforcement issues since till today, there seems to be a sharp distinction between Investor-State- Dispute Settlement (ISDS) by way of mediation, conciliation and arbitration on the one hand and judicial redress by national courts (of home, host or third States) on the other.